ODTWORZENIE WARUNKÓW WODN YCH OSUSZONYCH JEZIOR W POLSCE – WYBRANE PRZYKŁADY - Ptak, Mariusz (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
In the past, human intervention in water relations focused mainly on draining wetlands and lakes. In general, this was aimed at increasing the area of agricultural land or creating new settlement areas. In the case of lakes, the consequence of such actions was to reduce their level and in many cases to completely dry them. The maintenance of appropriate, assumed environmental conditions requires, in the case of drainage systems, maintaining the high efficiency of the drainage system, which is time- and cost-intensive. Neglecting such an approach, or intentional actions in this respect may lead to the restoration (to a different spatial extent) of drained lakes. The examples presented in the paper indicate that this process is quite common. In the context of the need to expand the water retention of the country, a detailed search of such reservoirs should be carried out and their renaturalization should be considered.